Using 3D computer planning for complex reconstruction of mandibular defects. Issue 1 (December 2016) - Kirke, Diana; Owen, Randall; Carrao, Vincent; Miles, Brett; Kass, Jason
Abstract For complex reconstruction of osseous defects of the head and neck, three-dimensional (3D) computer planning has been available for over 20 years. However, despite its availability and recent refinements, it is a technology that has not been widely adopted. While 3D computer planning has been proposed to improve surgical precision, reduce operating time and enhance functional outcomes, the objective evidence supporting these claims is limited. Here we review the recent literature that supports the use of 3D computer planning for complex osseous defects of the mandible. We highlight a case example where 3D modeling played a critical role, particularly during the virtual surgical planning stage. Finally, we propose that routine post-operative 3D analysis become an essential element in determining operative success. Critical evaluation of outcomes will better define its use in complex reconstruction of osseous defects.